Public participation of renewable energy (Ppred) model in Malaysia: An instrument development - Abdullah W.M.Z.B.W.; Zainudin W.N.R.A.B.; Ishak W.W.B.M.; Sulong F.B.; Zia Ul Haq H.M. (Diponegoro university Indonesia - Center of Biomass and Renewable Energy (CBIORE), 2023)
Environmental technology; Multivariant analysis; Renewable energy resources; Sustainable development; Confirmatory factor analysis; Development model; Exploratory factor analyse; Factors analysis; Instrument development; Malaysia; Public participation; Renewable energies; Renewable energy development; Willingness to pay; Factor analysis